Sustainable Development at University of Pécs - K, Orbán; T, Kulcsár; B, Radvánszky (Journal of Sustainability Perspectives, 2021)
Since 2016, the University of Pécs (UP) has participated in the UI GreenMetric World University Ranking. Thanks to its conscious, disciplined environmental ambitions and related achievements, UP has been able to move forward year after year in the ever-expanding rankings and in 2019 it has been ranked among the top 100 greenest universities in the world. UP believes that sustainability must be achieved not only in its operations and university-related services but also in the internal and external natural, social and economic environment associated with the university. UP presents its sustainable development efforts along the lines of achievements in the natural, social and economic environment and explores its future visions. UP stated its mission, that every useful practice, innovation, management in the environment tend to help sustainability and sustainable administration has to be encouraged, with the aid of education and science aiming to strengthen ecological consciousness. It was realized in the spirit of this mission, the development of the 24,8 billion HUF Modern Cities Programme for the built infrastructure of UP, the award of the title "Responsible Employer of the Year" in 2019, the award of the "Energy Efficient Institution" award as the first Hungarian university and the award of the Baranya County Environmental Prize was achieved. In the social and economic environment, as an Energy Efficiency Mentor organization, UP established the Baranya Virtual Power Plant Program in 2019, which, together with social and economic actors, saved 3.5 MW of energy in the South Transdanubian region of Hungary within 1 year. With the support of the Visegrad Fund, UP is trying to build a network of universities between the Visegrad countries and the universities of the Danube Region, where the fight against climate change will become even more effective by means of shaping attitudes. The University of Pécs intends to increase its environmental ambitions in the future